Seismic isolator based on multilayer magnetorheological elastomer - Kumar S.; Jaafar M.F. (American Institute of Physics Inc., 2023)
Magnetorheological Elastomer, which is also known as MREs, has multiple usage of application as it has the ability to isolate the vibration by varying the stiffness with the presence of magnetic field. Based on this research, it explains about the fabrication of the isolator for multilayer MRE, in order to be tested for vibration isolation by obtaining graphs of time domain and frequency domain for isotropic and anisotropic MRE based on multilayer configuration with the aid of LabVIEW NXG. The samples of the MREs were prepared in a mold and cured for about 4 hours or over a night to have the best result of the sample. Both types of MRE samples were tested with variable configuration in order to analyse the differences in time domain and frequency domain graphs at different percentage of carbonyl iron particle (CIP) used in the MRE that was mixed with silicone rubber. Variable distance of curing was also implemented for anisotropic arrangement, in order to test the performance of the MRE for different magnetic field strength intensity. 2021 Author(s).